2015
DOI: 10.1002/mc.22294
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor 4α suppresses the aggravation of colon carcinoma

Abstract: Hepatocyte nuclear factor 4-α (HNF4α), a nuclear receptor, is expressed at lower levels in colon carcinoma tissues than in adjacent normal tissues. However, the relation between HNF4α and colon cancer progression and the underlying molecular mechanisms remain unclear. Here, we investigated the role of HNF4α in the progression of colon carcinoma. We showed that HNF4α mRNA and protein were downregulated in colon carcinoma specimens. HNF4α expression was related to pT classification (P < 0.001), lymph node metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…After reducing HNF4 α , protein ( Figure 4e ) and mRNA levels ( Figure 4f ) of PED increased in both cell lines. Next, we wanted to test if HNF4 α regulates cell migration 23 , 24 through PED. Therefore, we performed a rescue experiment and silenced PED and HNF4 α simultaneously in SNU-449 cells ( Figure 4g ).…”
Section: Resultsmentioning
confidence: 99%
“…After reducing HNF4 α , protein ( Figure 4e ) and mRNA levels ( Figure 4f ) of PED increased in both cell lines. Next, we wanted to test if HNF4 α regulates cell migration 23 , 24 through PED. Therefore, we performed a rescue experiment and silenced PED and HNF4 α simultaneously in SNU-449 cells ( Figure 4g ).…”
Section: Resultsmentioning
confidence: 99%
“…This gene has been shown to cause maturity-onset diabetes of the young 15 and has implications in liver and intestinal development. 16,17 Besides its physiological functions in normal colorectal tissue, expression of HNF4-a has been demonstrated in CRC, 18,19 intestinal-type ampullary cancer, 20 gastric cancer, [21][22][23][24] ovarian mucinous neoplasms 25 and IMA. 9 In our study we confirm that CRC metastases also exhibit HNF4-a expression frequently (96%).…”
Section: Discussionmentioning
confidence: 99%
“…1 (3) 25 (3) 1 (5) 25 (2) 10 (3) 16 (3) 1 (1) 25 (3) 15 (3) 10 (2) ADC, adenocarcinoma; mADC, mucinous adenocarcinoma; ASC, adenosquamous carcinoma; CDX-2, caudal type homeobox transcription factor 2; CK, cytokeratin; HNF4-a, hepatocyte nuclear factor 4 alpha; IMA, invasive mucinous adenocarcinoma; LC, large cell carcinoma; PC, pleomorphic carcinoma; SATB2, special AT-rich sequence-binding protein 2; TTF-1, thyroid transcription factor-1. (15) 42 (12) 29 (23) 7 (20) 65 (15) 55 (13) 16 (27) pT3 68 (14) 1 (11) 67 (14) 4 (19) 64 (14) 3 (18) 65 (14) 44 (13) 24 (19) 2 (6) 66 (15) 54 (13) 84 (19) 1 (6) 84 (18) 59 (17) 26 (21) 5 (14) 80 (18) 70 (17) 13 (3) 1 (6) 13 (3) 10 (3) 4 (3) 1 (3) 13 (3) 12 (3) 1 (2) Stage IA (17) 3 (18) 74…”
Section: S T a T I S T I C Smentioning
confidence: 99%
“…But studies have illustrated, in small intestine and colon cancer, loss of HNF4α activated the WNT/β-catenin signaling pathway. In these cancer tissues, HNF4α was low expressed compared with adjacent normal tissues ( Cattin et al, 2009 ; Yao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that knockdown of HNF4α decreased significantly the protein and mRNA expression levels of WNT5A, cytoplasmic β-catenin and cyclinD1 in vitro , and increased significantly the expression of E-cadherin comparing with control cells. HNF4α was reported to compete with β-catenin for binding to TCF4, regulating Epithelial-to-mesenchymal transition (EMT) ( Yao et al, 2016 ). Loss of E-cadherin is regarded as a major conventional marker of the EMT ( Alotaibi et al, 2015 ; Yamashita et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%